A Phylogenetic Codon Substitution Model for Antibody Lineages. Issue 1 (1st May 2017) - Hoehn, Kenneth B; Lunter, Gerton; Pybus, Oliver G
Abstract: Phylogenetic methods have shown promise in understanding the development of broadly neutralizing antibody lineages (bNAbs). However, the mutational process that generates these lineages, somatic hypermutation, is biased by hotspot motifs which violates important assumptions in most phylogenetic substitution models. Here, we develop a modified GY94-type substitution model that partially accounts for this context dependency while preserving independence of sites during calculation. This model shows a substantially better fit to three well-characterized bNAb lineages than the standard GY94 model. We also demonstrate how our model can be used to test hypotheses concerning the roles of different hotspot and coldspot motifs in the evolution of B-cell lineages. Further, we explore the consequences of the idea that the number of hotspot motifs, and perhaps the mutation rate in general, is expected to decay over time in individual bNAb lineages.